The Environmental Kuznets Curve Hypothesis in Industrialized Countries: A Second Generation Econometric Approach - Mekhzoumi, Lotfi; Harnane, Nadjoua; Ayachi, Abdellah; Abdellaoui, Okba (International Journal of Economics and Financial Issues, 2022)
This study contributes to the analysis of the Environmental Kuznets hypothesis (EKC) for 31 industrialized countries during 1980-2019 using long-term static and dynamic panel data methods. According to Pesaran’s CD tests, the CSD issue is present in all variables. The EKC model had a long-run relationship, according to the results of the second-generation Pesaran CIPS unit roots and Westerlund tests. The estimation results of the static model (MG) and dynamic models (CS-DL and CS-ARDL) reached the same conclusion as the reliability of the EKC hypothesis, implying that environmental pollution and economic growth are linked in an inverted N-letter shape.